Business strategy formulation using quantitative strategic planning matrix on PT PPSU (Perseroda) - Yunir, Refli; Sembiring, Meilita Tryana; Nazaruddin, Nazaruddin (Institute of Computer Science (IOCS), 2024)
The good performance of the PT PPSU company can have a positive impact on the revenue of the Sumatra Utara region. The management continues to strive for improvements in financial and non-financial performance. One of the efforts is through strategizing. The researcher intends to analyze the formulation of alternative strategies in the company using the Quantitative Strategic Planning Matrix (QSPM). The location of this research is in Medan City, Sumatra Utara Province. The informants in this study were determined purposively. The data used are primary data collected during the survey and secondary data documented from various credible sources. Factual conditions are analyzed descriptively while strategy formulation is analyzed using SWOT and QSPM. The results of the analysis of the company's internal and external factors found four company strengths, three weaknesses, six opportunities and three threats. The use of the SWOT matrix finds nine alternative strategies, and by using the QSPM method obtained a sequence of priority strategies that the company can do. Priority strategies one and three are aggressive/expansion strategies. While the second priority strategy is a diversification strategy.